Pengaruh Kebijakan Kepala Daerah, dan Pembangunan Ekonomi Pedesaan terhadap Kesejahteraan Masyarakat : (Studi Kasus Kecamatan Pabedilan Kabupaten Cirebon) - Risma Amelia; Roni Roni; Mohamad Badrun Zaman; Dumadi Dumadi; Anisa Sains Kharisma (BADAN PENERBIT STIEPARI PRESS, 2025)
This study was conducted to examine the influence of Regional Head Policies and Rural Economic Development on Community Welfare in Pabedilan Subdistrict, Cirebon Regency. The purpose of this research was to determine the partial and simultaneous effects of these two independent variables on community welfare. The analysis was carried out using the SPSS program. The results of the partial correlation analysis revealed a positive and strong influence between regional head policies and community welfare (r = 0.746), as well as a positive and very strong influence between rural economic development and community welfare (r = 0.831). Simultaneously, an R value of 0.859 was obtained, indicating a strong relationship, with a coefficient of determination (R²) of 0.738. This indicates that 73.8% of the variation in community welfare can be explained jointly by regional head policies and rural economic development, with a significant and strong effect.